2001
DOI: 10.1007/bf02234373
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of the value of anorectal physiology in the management of fecal incontinence

Abstract: Anorectal physiology testing is useful in the evaluation of patients with fecal incontinence. Without the information obtained from physiologic testing, 11 percent of patients who may have benefited from surgery would not have been given this option, and 7 percent of patients could have potentially undergone unnecessary surgery. Transanal ultrasound is the study most likely to change a patient's management plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 19 publications
0
33
0
3
Order By: Relevance
“…It is also known that the clinical manifestations presented by patients with anal incontinence may not correlate with the results of tests performed. That is, patients with very severe symptoms may present tests with few or mild changes, whereas some patients may experience mild symptoms with quite altered tests (17) . This highlights the lack of clinical correlation of incontinence symptoms with the results of objective tests, which may be associated with psychological factors, or even social, impacting quite differently, the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that the clinical manifestations presented by patients with anal incontinence may not correlate with the results of tests performed. That is, patients with very severe symptoms may present tests with few or mild changes, whereas some patients may experience mild symptoms with quite altered tests (17) . This highlights the lack of clinical correlation of incontinence symptoms with the results of objective tests, which may be associated with psychological factors, or even social, impacting quite differently, the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies suggest that findings on physiology testing do not consistently correlate with severity of FI or prediction of outcome [14,15]. Endoanal ultrasonography may be a useful tool for identifying patients with complete sphincter disruption and allow the surgeon to choose between the options of sphincter repair or SNM.…”
Section: Discussionmentioning
confidence: 99%
“…Though the goals of these testing modalities are to correlate objective findings with selection for particular treatment modalities, data from these studies have not been consistently shown to correlate with the severity of FI or prediction of outcomes following treatment with traditional management algorithms [12][13][14][15][16]. The purpose of this study was to investigate whether anorectal physiology testing or transanal ultrasonography may predict patient response to treatment with SNM.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] Anorectal testing can guide management particularly when surgical options are being considered. 47 Test results should be interpreted together with clinical features. The indications, modalities, and utility of testing will continue to evolve as newer therapeutic options become available.…”
Section: Summary and Role Of Testing In Clinical Practicementioning
confidence: 99%